Surgery-induced and Associated Long-term Strictures - Freeman, Matthew J.; Praska, Corinne E.; Sanger, Cristina B. (Clinics in Colon and Rectal Surgery, 2025)
Strictures, commonly referred to as stenoses, are a rare but significant complication for patients who have undergone colorectal surgery. Strictures are difficult to diagnose due to variable clinical presentations, diverse etiologies, and lack of formalized diagnostic criteria. The clinical impact of strictures can be quite variable, ranging from a benign course not requiring intervention to emergent complications (e.g., bowel obstruction, perforation). Importantly, strictures can also have a large impact on patient quality of life and long-term bowel function. Once a stricture is diagnosed or clinically suspected, it is critical to determine its etiology to help guide clinical management and prevent recurrence. Strictures can be categorized as partial or complete, intrinsic or extrinsic, benign or malignant. We propose the ARCTIC mnemonic (Anastomosis, Radiation/Chemotherapy, Technical, Inflammation, and Compression) as a useful tool for remembering common stricture causes in the postoperative environment. This review seeks to provide an overview of the etiologies, diagnosis, and management of strictures in the postoperative setting.
Keywords: stricture; anastomosis; obstruction; complication; stenosis